Development of standard sizing for female high school students of the University of the Philippines Integrated School - Rita, Karmela Ruby Lustre; Lumawig, Maria Josephine Trono (Quezon City College of Home Economics, University of the Philippines Diliman, 2011)
The study aimed to develop a standard sizing for the upper torso that will fit the needs of adolescent females, in particular, the high school students of the University of the Philippines Integrated High School. Using Stratified Random Sampling, the study focused on 80 female adolescents within the regular secondary education, ages 12 to 16, of the University of the Philippines Integrated School. The research used a descriptive research design method. Respondents were measured for different measurement points of the upper torso needed in developing the standard sizing and the front and back bodice patterns. The study developed a standard sizing base from actual measurements of female high school students and created bodice and sleeve patterns that would conform to the sizing specifications of the three (3) basis sizes: Small (S), Medium (M) and Large (L). This standard sizing did not cover the wide range of actual upper torso measurements of the 80 students included in the sample. With the analysis of the standard sizing developed through commercial grading, the researcher developed a second sizing by increasing and widening the grading increment for each size. In the second sizing, Small, Medium, Large, and Extra Large were developed to cover the wide body measurement ranges of the students in the sample. It is a relevant aspect of the study if the sizing developed be compared to the presently used commercial standard sizing used for the female adolescent market in the garment industry. Moreover, a related study on the upper torso proportions, symmetry, and figure types of the students can also be significant.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing and dress measurements -- Philippines -- Standards; School children's clothing -- Philippines